IMPROVING TEACHERS' COMPETENCY IN DESIGNING INSTRUCTIONAL MEDIA FROM ANORGANIC WASTE - Nurmaini Nurmaini (Laboratorium Program Studi Pendidikan Guru Sekolah Dasar FKIP Universitas Riau, 2021)
This research was motivated by the need for learning which demanded the teacher not only to be proficient in teaching but also to facilitate students’ learning activities in order to create student-centered learning. This study aimed to improve teachers’ competence in designing instructional media, in this case media from anorganic materials. This research was conducted at SDN 11 Bathin Solapan involving 18 teachers as the subjects of the research. The instrument in this study was an observation sheet. The results showed that in Cycle I, the teachers’ competence in designing media was 67.13% and it increased to 74.54% in Cycle II with good criteria. Based on the results of the study, it was concluded that providing guidance improved teachers’ competence at SDN 11 Bathin Solapan in designing intstructional media from anorganic materials.